Application of national Indoor Air Quality Standard and its obstacles in China: a cross-sectional survey - Xia ZHANG; Yi XU; Jian-hui GAO (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo examine the application of national Indoor Air Quality Standard - GB/T 18883 - 2002 (IAQS) and its obstacles and to provide references for revising the standard.MethodsUsing stratified multistage sampling, we conducted a questionnaire survey among 91 professional institutions in 26 cities across China during July - October 2019. The selected institutions included centers for disease control and prevention, health supervision institutes, housing and construction companies, detection agencies, industry associations, and universities. Information on IAQS-related awareness and concern among the public were also collected from 1 052 valid responses in all provincial-level regions of mainland China simultaneously.ResultsValid information were collected from all the institutions selected. The IAQS was mainly applied by detection agencies and daily application of the IAQS was reported by 18.68% of institutions surveyed. In indoor air quality assessment performed by the institutions, the most commonly adopted indicators of the IAQS was formaldehyde (being adopted in 91.21% of the assessments reported), followed by benzene (68.13%), ammonia (62.64%), toluene (57.14%), and total volatility organic compounds (TVOC) (57.14%). There were 31% of the surveyed institutions reporting being able to conduct less than 10 of 19 indicators included in the IAQS. Of all the institutions, 91.21% were reported with the capability of detecting formaldehyde in routine monitoring, but only 28.57% with the capability of benzo(α)pyrene detection. Stratified indicator management, including the particulate matter less than 2.5 μm in aerodynamic diameter (PM2.5) as a quality index, and appropriate optimization of sampling and analyzing instrument were among the most frequent recommendations proposed by the institutions for the revision of the IAQS. Among the surveyed citizens, 43.82% reported the awareness about the IAQS and 73.8% reported the concern on indoor air.ConclusionThe national Indoor Air Quality Standard - GB/T 18883 - 2002 is generally reasonable and mainly adopted by detection agencies in daily routine indoor air quality assessment. Improvements in indicator selection and analysis instrument were suggested by professional institutions for the revision of the standard